THE INFLUENCE OF FAMILY ENVIRONMENT AND LEARNING INTEREST ON SOCIAL STUDIES LEARNING OUTCOMES OF NINTH GRADE STUDENTS AT SMP NEGERI 4 PEMATANGSIANTAR - Elsy Hariani Saragih; Injen Pardamean Butar-butar; Herlina Hotmadinar Sianipar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The problem in this study is the low learning outcomes of students in Social Studies subjects, which are presumed to be influenced by the family environment and low learning interest of ninth grade students at SMP Negeri 4 Pematangsiantar. This research is a quantitative study using a descriptive method. The population consisted of all ninth-grade students across 10 classes, totaling 319 students. The sample was determined using proportional random sampling, resulting in 80 respondents. Data were collected through questionnaires for the variables of family environment and learning interest, as well as documentation of Midterm Examination (UTS) scores in Social Studies as indicators of learning outcomes. The data analysis techniques employed included simple linear regression, multiple linear regression, t-test, F-test, and the coefficient of determination. The assumption test for analysis was conducted using the chi-square normality test, and the results indicated that both variables were normally distributed. The analysis showed that there is a positive and significant influence of the family environment on students’ learning outcomes (tcount = 3.43 > ttable = 1.664) and a positive and significant influence of learning interest on students’ learning outcomes (tcount = 2.022 > ttable = 1.664). The F-test results revealed that both variables simultaneously have a significant effect on students’ learning outcomes (Fcount = 4.463 > Ftable = 3.96). The coefficient of determination (R²) of 0.95574 indicates that 95.574% of the variation in students’ learning outcomes is influenced by the family environment and learning interest, while the remaining 4.426% is influenced by other factors not examined in this study.